Teaching and learning chinese as a heritage language (CHL) - Zhang, Huichao; Gong, Yang; Zhang, Luyao; Gao, Xuesong (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Research on Chinese heritage language (CHL) education has flourished in recent decades, driven by the increasing presence of CHL learners in schools worldwide, especially in multiethnic and multilingual contexts such as the USA, Canada, and Australia. This article presents the findings of a systematic review of 53 empirical studies on CHL education indexed in the Social Science Citation Index (SSCI) and published from 2008 to 2023. The study reveals that CHL research primarily focuses on four core areas: CHL maintenance, CHL acquisition, CHL pedagogy, and CHL learners’ identity. The research methodologies within the existing literature show a predominance of quantitative studies, particularly laboratory-based research on CHL acquisition, and the results highlight the critical role of the home environment in supporting CHL maintenance. This review concludes with recommendations for advancing future research on and pedagogy practices of CHL. Specifically, CHL education needs to incorporate sociolinguistically-informed pedagogical approaches and materials and implement valid assessment tools to address the diverse needs and interests of CHL learners. Future research should further investigate how CHL learners’ ethnic identities are shaped by and interact with gender, socio-economic status, and dialect backgrounds, while assessing tailored interventions and engaging in classroom-based action research to enhance pedagogy and longterm language transmission across generations
Keywords: Chinese heritage language (CHL); systematic review; heritage language learner identity; heritage language maintenance; language pedagogy